EXPERIENCE OF INSTRUCTIONAL DESIGNING THE CONTENT OF MASTER'S STUDENTS' PREPARATION IN THE EDUCATIONAL EXPERTISE AREA - Marianna Arutyunyan (Вестник Северо-Кавказского федерального университета)
The article presents targeted and substantive aspects of instructional design of master's students' preparation in the field of «Pedagogic Education» in the educational expertise area.